TRIMming Type I Interferon-Mediated Innate Immune Response in Antiviral and Antitumor Defense - Ling Wang; Shunbin Ning (Viruses, 2021)
The tripartite motif (TRIM) family comprises at least 80 members in humans, with most having ubiquitin or SUMO E3 ligase activity conferred by their N-terminal RING domain. TRIMs regulate a wide range of processes in ubiquitination- or sumoylation-dependent manners in most cases, and fewer as adaptors. Their roles in the regulation of viral infections, autophagy, cell cycle progression, DNA damage and other stress responses, and carcinogenesis are being increasingly appreciated, and their E3 ligase activities are attractive targets for developing specific immunotherapeutic strategies for immune diseases and cancers. Given their importance in antiviral immune response, viruses have evolved sophisticated immune escape strategies to subvert TRIM-mediated mechanisms. In this review, we focus on their regulation of IFN-I-mediated innate immune response, which plays key roles in antiviral and antitumor defense.